Scholastic atlas of space - Vekteris, Donna; Pelletier, Carl (New York : Scholastic Reference, 2004)
Presents a collection of facts and data about the solar system and other galaxies, nebulas, dark holes, the Milky Way, and the sun and includes star maps.
Includes index.
Horn Book.
Library Media Connection.
School Library Journal.
6.2
3-6
Keywords: Astronomy -- Charts, diagrams, etc -- Juvenile literature; Astronomy -- Juvenile literature; Astronomy; Astronomy